2015
DOI: 10.1007/s00432-015-1937-y
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of bromodomain PHD-finger transcription factor in colorectal carcinoma and association with vimentin and E-cadherin

Abstract: Our results strongly suggested that the high BPTF expression was significantly correlated with tumor progression and may be a potent prognostic marker of CRC. Moreover, BPTF expression was significantly associated with EMT markers vimentin and E-cadherin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 26 publications
6
33
1
Order By: Relevance
“…Higher levels of mRNA of bromodomain PHD finger transcription factor was observed in 85% of tumor samples compared to controls. The results of Western blot confirmed the mRNA expression results and also 67.6% of samples showed high levels resulted from immunohistochemistry . Stomatin is a cell membrane protein whose function is unclear, but it may be involved in the regulation of ion channels and transporters.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Higher levels of mRNA of bromodomain PHD finger transcription factor was observed in 85% of tumor samples compared to controls. The results of Western blot confirmed the mRNA expression results and also 67.6% of samples showed high levels resulted from immunohistochemistry . Stomatin is a cell membrane protein whose function is unclear, but it may be involved in the regulation of ion channels and transporters.…”
Section: Resultssupporting
confidence: 69%
“…Bromodomain PHD finger transcription factor has been identified to play a possible role in transcription. Upregulation of this protein has been reported in colorectal cancer . Twenty samples of colorectal cancer were compared with controls and the levels of mRNA and protein were analyzed using RT‐PCR, Western blot analysis and immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…During EMT, epithelial cell lose its E-cadherin expression, which contributes to intercellular adhesion and enables cells with migratory and invasive properties. Increase expression of N-cadherin, Vimentin and Fibronectin can be markers for metastasis and poor prognosis [12–14]. EMT has been demonstrated to be a good target for various therapeutic interventions [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…EMT further plays an important role in many cancers, such as breast cancer, lung cancer, pancreatic cancer and skin squamous cell carcinoma. It is showed that Vimentin may correlated with cancer progression and prognosis at the invasive frontier in many kinds of cancers[23]. …”
Section: Discussionmentioning
confidence: 99%